The River Congo - Africa's sleeping giant: Regional integration and intersectoral conflicts in the Congo Basin - Tobias von Lossow (Stiftung Wissenschaft und Politik (SWP), 2017)
Making greater of use of the waters of the Congo could boost development across - and beyond - the region, but threatens to favour particular users' interests at the expense of others. Within its enormous catchment area, the Congo is the dominant transport network and the lifeblood of the African rain forest, upon which millions depend for their livelihoods. Tapping the river's resources could significantly improve the region's water and food supplies, while its hydro-energy potential could theoretically satisfy the electricity needs of the entire continent. Plans to construct more major dams at the Inga Falls demonstrate that the ten Congo Basin states are pursuing common goals - but also having to deal with sharpening intersectoral conflicts. An inconsistent line on dam-building makes it harder for Germany to play a constructive role in these development processes.
Keywords: 320